First-time- and repeat testers for HIV : a demographic and HIV prevalence comparison amongst clients at mobile HIV Counselling and Testing sites in Tshwane, South Africa - Van Ginneken, Jeroen K. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2013.